Pictorial Race Activation in Priming Measures. Issue 4 (3rd July 2016) - Stepanova, Elena V.; Strube, Michael J.; Clote, Laura E.; Limes, Daniel
ABSTRACT: This review explores characteristics of facial primes employed in priming studies of racial prejudice and stereotyping. It addresses the role of perceptual, cue-based processing of visual stimuli characteristics in altering racial typicality, and the effects of different moderators. The authors document the nature of variability in primes and moderators used in priming studies ( N = 96) up to 2009. Methodological and conceptual implications are discussed, along with gaps in the field. Better control over facial primes employed, more accuracy in reporting and open access to procedural information are suggested in an effort to improve the state of racial priming research.